The effect of genotype of the plant-host on the morpho-cultural properties of Septoria leaf blotch agents - Yu. Z. Zeleneva; V. P. Sudnikova (Зерновое хозяйство России)
Leaf blotch is the most harmful diseases of wheat on the territory of the Central-Blackearth region which result in great harvest losses. Septoria leaf blotch is the most widely spread among all. Epiphytoty caused by Septoria leaf blotch which leads to great losses of harvest (more than 20%) is possible four times every 10 years on the territory of the Central-Blackearth region. Natural populations of Septoria and Stagonospora are heterogeneous due to morpho-cultural and virulent properties. The object of the study was the infected material of pathogens, obtained from the sowings of regional wheat varieties in various agroclimatic parts of the CBeR. The obtained data are necessary to develop a substantiated breeding program for septoria resistant varieties. The complex of septoria pathogens is represented by three types of septoria fungi in the region; they are Septoria tritici Rob et. Desm., Stagonospora avenae f. Sp. Triticea Jhons., Stagonospora nodorum [Berk] Castellani & E. G. Germano. The species Septoria tritici Rob et. Desm. was taken as the most widely spread pathogen of wheat leaf blotch to study intravarietal variability. To study intravarietal variability of pathogen according to morpho-cultural traits there was carried out an analysis of isolates in three main criteria: appearance and structure of the colonies, speed of colonies growth in the nutrient surrounding, intensity of fungi sporulation. In studying the biological properties of the population, the special attention was paid to the role of the variety-host in the formative process. There was a dependence of the morphotype of the pathogen colonies on the ploidy of the variety-host. The frequency of occurrence of S. tritici colonies types selected in the varieties of soft and durum wheat was different. There was no influence of variety-host ploidy on the speed of growth of morphological types of isolate colonies S. tritici. Average growing colonies dominated in the population. On the basis of the obtained data we decided that a way of life of the variety-host (spring and winter wheat) had no significant effect on the formation of high sporulated isolates.